Phytochemical studies and biological activity of goniothalamus macrophyllus - Nurfarahen, Binti Jamil (Universiti Malaysia Sarawak, UNIMAS, 2012)
Phytochemical and biological studies have been carried out on the extract obtained from the leaves of Goniothalamus macrophyllus. Extraction using methanol gave dark green extract of 33.27 g (7.25%). Solvent partition was carried out using solvents with increasing polarity in the order of hexane, dichloromethane and ethyl acetate. Isolation and purification were performed on dichloromethane and methanol partition using column chromatography. Two semipure compound namely Compound 1 and Compound 2 corresponding to molecular mass of 128 g/mol and 200 g/mol, respectively were isolated. Compound 1 was isolated as white crystal needle with melting point in the range of 115.0-117.0 C and Rf value of 0.52 in dichloromethane:ethyl acetate (1:1). Infrared spectrum revealed strong absorption band at frequency 1689 cm-1 that was assigned to C=O. Based on the NMR spectrum, the compound have 11 protons and 10 carbons. Due to impurities, the information was not enough to elucidate the structure of Compound 1. Compound 2 was isolated as white solid with melting point in the range 84.5-86.0 C and Rf value of 0.82 in dichloromethane. Based on the 1H and 13C NMR spectrum, it indicates there were 12 protons and 13 carbons. Based on the spectral data on published data, Compound 2 has been identified as goniothalamin. The brine shrimp toxicity test showed that none of the extracts were toxic to Artemia salina.